Colloquial Korean the complete course for beginners - Ooyoung Pyun, Danielle; Kim, In-Seok; Routledge (Firm) (Boca Raton, FL : Routledge, 2010)
The course offers a step-by-step approach to written and spoken Korean. No prior knowledge of the language is required
Title from container
Keywords: Korean language -- Study and teaching; Korean language